A Reviewed Approach to the 5G Mobile Technology - Rathore, Vishal Singh; Chauhan, Alka (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
5G or the 5th generation of mobile technology, is a name used in many research papers and projects to denote the next phase after the upcoming 4G standards. Currently the term 5G is not official. In this generation researches are being made on WORLD WIDE WIRELESS WEB (WWWW), DYNAMIC ADHOC WIRELESS NETWORKS (DAWN) and REAL WIRELESS WORLD. New standard technology releases are in development beyond 4G but are not considered as new mobile technologies, because 4G implementation and complaint handling regarding the 4G system are still under development. This paper is focused on network Architecture of 5G Technology and evolution from 1G to 5G. The fifth generation will provide very high speed and affordable broadband wireless connectivity and services like documentation, supporting e-transactions etc.